THE ROLE OF BK TEACHER IN DIRECTING CLASS XII STUDENTS TO CONTINUE HIGHER EDUCATION THROUGH PLACEMENT AND DISTRIBUTION SERVICES AT MAN SIBOLGA - Arifany, Anjani Farras; Manurung, Purbatua (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
The purpose of this research is to determine the role of BK (Guidance and Counseling) teachers in guiding twelfth-grade students to pursue higher education through placement and allocation of services at MAN Sibolga. This study employs a qualitative descriptive research design. The research sample was taken using purposive sampling and snowball sampling techniques, consisting of three students from three different classes. Data collection was conducted through interviews. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research findings are as follows: 1) The role of BK teachers in guiding twelfth-grade students to pursue higher education through placement and allocation services at MAN Sibolga is carried out effectively, and some students have started to make decisions about their post-high school education, 2) BK teachers play a role in assisting students by providing input on higher education options after high school, and 3) by implementing placement and allocation services to guide students in pursuing higher education, students are expected to be able to choose their own further education based on their own preferences, rather than feeling forced or following their peers.